Вікова структура репродуктивної частини популяції озерних жаб Pelophylax ridibundus (Ranidae, Amphibia) - Ремінний, В.Ю. (Національний Науково-природничий музей НАН України, 2007)
Методом скелетохронологии исследована выборка озерных лягушек Pelophylax ridibundus численностью 15 самцов и 12 самок. Показано, что самцы достигают половой зрелости на год раньше самок, после третьей зимовки. Основу репродуктивной части популяции составляют самцы 4–6 и самки 5–6-летнего возраста. На протяжении жизни самцы принимают участие в размножении трижды, а самки – дважды. Установлено, что исследованная популяция полностью обновляется в течение 6–7 лет. It has studied the sample of the march frog Pelophylax ridibundus with total number of specimen – 15 males and 12 females by skeletochronology method. It has shown that males attain the sex maturity (puberty) in one year earlier then females, after third wintering. The basis of the reproductive part of population is 4–6 years old male and 5–6 years old female. During theirs lifes, males take part in reproduction three times and females just two times. It has established that studied population completely renovate during 6–7 years.